Influence of polyvinylpyrrolidone as stabilizing agent on Pt nanoparticles in Pt/H-BEA catalyzed hydroconversion of n-hexadecane. (1st June 2022) - Romero, Douglas; Oropeza, Freddy; Rigutto, Marcello; Hensen, Emiel J.M.
Highlights: Pt-loaded Beta zeolite obtained by colloidal approach with PVP as capping agent. Residual carbonaceous species from PVP affect catalytic performance. Decreased acidity leads to better acid/metal balance in paraffins hydrocracking. Abstract: Colloidal Pt particles prepared using polyvinylpyrrolidone (PVP) as a capping agent were loaded on acidic Beta zeolite, with the aim of obtaining bifunctional catalysts with controllable dispersion for the hydroconversion of n-hexadecane (n-C16 ). Among the different approaches to remove PVP, reduction was the most effective whilst maintaining the initial Pt particle size after deposition on the zeolite. The presence of small amounts of nitrogen- and carbon-containing products from PVP decomposition affected the acidity stronger than the Pt metal function. Therefore, it was not possible to establish the effect of Pt particle size on the performance of the Pt/Beta zeolites in n-C16 hydroconversion and the performance trends were dominated by the acidity differences. Small Pt particles on zeolite obtained by using high PVP/Pt ratios during the colloidal synthesis step presented lower Brønsted acidity than catalysts containing larger Pt particles. The resulting variations in Pt/H + ratios led to a transition of observed ideal cracking behavior for weakly acidic catalysts (small Pt particles, larger amount of PVP residuals) to overcracking behavior for catalysts with stronger acidity. We find that the Pt/H + ratio and the number of acid-catalyzed steps extrapolated to zero conversion are better indicators of ideal cracking behavior than the isomers yield.